FDI-Led Growth and Environmental Trade-Offs in Morocco: Long-Run Cointegration and Dynamic Evidence - Fayou, Hamid; Boubrahimi, Nabil (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study provides a comprehensive analysis of the theoretical frameworks and quantitative effects of Foreign Direct Investment (FDI) in developing economies, commonly referred to as the Global South. By integrating robust methodological approaches Vector Error Correction Model (VECM) analysis—this research examines the multi-faceted impact of FDI on economic growth, environmental sustainability, and energy consumption. The findings indicate a complex, non-linear relationship between FDI and key economic variables, often mediated by local institutions, absorptive capacities, and sectoral characteristics. The results confirm a U-shaped relationship between FDI and renewable energy consumption globally, where initial effects may be negative but turn positive over time as economies develop and integrate advanced technologies . Furthermore, the analysis reveals that the interaction between FDI and economic growth significantly affects renewable energy consumption, aligning with the trade-off theory and race-to-the-bottom hypothesis rather than the conservation hypothesis . For policymakers, this integrated analysis offers valuable insights for designing strategic policies that maximize FDI benefits while mitigating potential negative externalities, particularly in environmental domains where the pollution haven hypothesis remains a contested framework